Human Resources and Payroll in China - Dezan Shira & Associates; Devonshire-Ellis, Chris; Fleming, Christian; Ku, Eunice; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Chinese law places significant obligations on employers to remain legally compliant in all labor matters. In this guide, we address the major issues in managing employment relationships in China. Including: Recruiting Professionals Hiring Staff Handling Payroll Managing the Employment Relationship Terminating the Employment Relationship Organizing Visas Within these topics, we address labor contracts, company rulebooks, salary packages, social insurance contributions, special circumstances for employees (extended sickness or pregnancy), termination and severance pay, and visas for foreign staff and Chinese staff being sent to work abroad.
Recruiting Professionals -- Hiring Staff -- Handling Payroll -- Managing The Employment Relationship -- Terminating The Employment Relationship -- Organizing Visas.
Keywords: Economics; Industrial management; Economics/Management Science; Management/Business for Professionals; Human Resource Management